Puasa dan Gaya Hidup Sehat, Tafsir Tematik QS. Al-Baqarah: Penelitian - Iqbal Syaifudin; Ainur Rhain (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article explores the relationship between fasting in Islam and the concept of a healthy lifestyle, based on verses QS. Al-Baqarah 183–185. In today’s modern era, unhealthy lifestyles have led to increased physical and mental health issues. Fasting, as a spiritual practice, also provides psychological and physiological benefits such as emotional regulation, reduced stress hormone (cortisol), improved metabolism, and cell regeneration. The study employs a thematic approach to the Qur’anic verses, supported by psychological and health science perspectives. The findings indicate that fasting not only nurtures the soul towards achieving piety but also serves as a natural strategy for physical and mental balance. Fasting in Islam is more than a spiritual ritual it is a holistic healing system relevant to contemporary healthy living challenge.